Assessment of IL-6 activity in cervico-vaginal mucus connected with cervical length concerning elderly pregnant women over 35 years of age at a risk of preterm delivery - Pawłowicz, Paweł; Rawski, Wojciech; Grzebyk, Katarzyna; Stetkiewicz, Tomasz; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
Inerleukin-6 is a pleiotropic cytokine with multidirectional influence on the cells of both innate and adaptive immune system. The main role of IL-6 is to initiate and regulate acute inflammatory response and adaptive immunity. It has a number of physiological effects. Overproduction of IL-6 causes a change from acute to chronic inflammation. Its higher concentration may initiate premature occurrence of preterm uterine contractions. Preterm delivery is the main reason for perinatal mortality and morbidity of neonates. Pro-inflammatory cytokines, mainly IL-1 and IL-6, which stimulate prostaglandin production are considered to be crucial reasons for preterm delivery.